2014
DOI: 10.1038/srep05970
|View full text |Cite
|
Sign up to set email alerts
|

Novel VCP modulators mitigate major pathologies of rd10, a mouse model of retinitis pigmentosa

Abstract: Neuroprotection may prevent or forestall the progression of incurable eye diseases, such as retinitis pigmentosa, one of the major causes of adult blindness. Decreased cellular ATP levels may contribute to the pathology of this eye disease and other neurodegenerative diseases. Here we describe small compounds (Kyoto University Substances, KUSs) that were developed to inhibit the ATPase activity of VCP (valosin-containing protein), the most abundant soluble ATPase in the cell. Surprisingly, KUSs did not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 34 publications
8
91
2
Order By: Relevance
“…In our previous studies, KUS121 showed significant neuroprotective effects in rd10 mice, rd12 mice, and mutated rhodopsin transgenic rabbits, which are models of retinitis pigmentosa1719. Similar results were obtained using three different mouse models of glaucoma but without observable side effects18.…”
Section: Discussionsupporting
confidence: 68%
“…In our previous studies, KUS121 showed significant neuroprotective effects in rd10 mice, rd12 mice, and mutated rhodopsin transgenic rabbits, which are models of retinitis pigmentosa1719. Similar results were obtained using three different mouse models of glaucoma but without observable side effects18.…”
Section: Discussionsupporting
confidence: 68%
“…Because many proteins require ATP, a reduction of ATP levels would contribute to a functional decline in affected cells or organs in the early stages of the disease. Reducing ATP consumption by way of KUSs and/or enhancing ATP generation by yet-unknown compounds would be a novel strategy to retard these processes and thus to prevent or retard the progression of clinical manifestations [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…4h ) showed that KUS treatments had the potential to prevent or delay the disease progression. When examined by electron microscopy, the outer segment of the control rd10 mouse retina was mostly disarranged at the age of 21 days, whereas that of the KUS-treated rd10 mouse retina was regularly arranged [ 22 ].…”
Section: Kuss Mitigated Pathologies Of Rd10 a Mouse Model Of Retinitmentioning
confidence: 99%
“…Although SD-OCT is a noninvasive technology that allows us to investigate the morphological characteristics of various retinal diseases [20,21], it is impossible to directly evaluate the pathological features. In contrast, animal models associated with known gene mutations provide strong evidence that facilitate our understanding of the relationship between the SD-OCT findings and the pathological background [22][23][24][25][26][27][28][29][30][31][32]. However, to our knowledge, no study has assessed the relationship between SD-OCT findings and the origin of the structural changes in Rdh5 -/mice.…”
Section: Introductionmentioning
confidence: 99%